IMPLEMENTASI TATA KELOLA TEKNOLOGI INFORMASI MENGGUNAKAN FRAMEWORK COBIT 5 PADA DIREKTORAT JENDERAL BEA DAN CUKAI - Farida Indah Riantini; Dadang Iskandar Mulyana (CKI ON SPOT, 2019)
Directorate General of Customs and Excise needs a breakthrough by using audit to manage information technology around it. Managing information technology are urgently needed for Directorate General of Customs and Excise in order to correct the past mistake, improve, and evaluate itself. The method that we were used to measure capability level in this study are COBIT 5 framework which develope by ISACA. This COBIT 5 focused on Deliver, Service, and Support (DSS) which cover Services, Security Management, Continuity, Services Support for Stakeholders, Data Management, and Operational Facility. This study are based on qualitative research and data sample. Data sample gained by doing survey on selective respondents whis is first hand user who involve at managing information technology process. The research indicate that the level of capability DJBC at domains DSS is 2.09, which means still at the level 2 (managed process), it means that the process has been implemented regularly, there is planning and monitored. So, it needed recommendation the target level to be achieved level 3 with by improving the documentation of the processes manage information technology and compile requirements, classification, and prioritization in service delivery and incidenthandling